2012
DOI: 10.1371/journal.pone.0044166
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cysteine with Obesity, Inflammatory Cytokines and Insulin Resistance in Hispanic Children and Adolescents

Abstract: ContextPlasma total cysteine (tCys) independently relates to fat mass in adults. Dietary cyst(e)ine promotes adiposity and decreases glucose tolerance in some rodent models, but alleviates insulin resistance in others.ObjectiveTo investigate whether the association of tCys with body fat extends to children at particular risk of obesity, and whether tCys is associated with insulin resistance and obesity-associated inflammation.MethodsWe explored the cross-sectional relations of fasting plasma tCys and related m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 43 publications
6
59
2
1
Order By: Relevance
“…Apart from cystathionine, none showed positive associations (7,9). SAM and SAH have not, to our knowledge, been investigated in the same context.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Apart from cystathionine, none showed positive associations (7,9). SAM and SAH have not, to our knowledge, been investigated in the same context.…”
Section: Introductionmentioning
confidence: 81%
“…Likewise, humans with CBS deficiency are lean with decreased plasma total cysteine (tCys) (6). In contrast, high-plasma tCys is associated with increased BMI and fat mass in children and adults (7)(8)(9). Feeding cystine to mice induces lipogenic enzymes, lowers metabolic rate, and increases visceral adiposity (10).…”
Section: Introductionmentioning
confidence: 99%
“…The subjects of the previous study also had lower BMI (mean 6 SE: 21.8 6 2.6) than in the current study (median: 25.8; IQR: 23.9-28.6). Several studies have shown an association between serum cysteine and obesity and metabolic syndrome (34)(35)(36)(37). Furthermore, the Linxian population consisted mostly of subsistence farmers, whereas members of the ATBC study population had a more-ample and varied diet.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of plasma SAAs is generally associated with an unfavorable lipid profile, and plasma total cysteine is independently associated with body mass index (BMI) [12]. Another study reported that higher plasma total cysteine was associated with an increased risk of obesity and IR in Hispanic children and adolescents [13]. Rodent studies verified that cysteine supplementation increases weight gain despite reduced or consistent food intake [14-16].…”
Section: Introductionmentioning
confidence: 99%